Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.21077/ijf.2016.63.3.48294-19
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the freshwater murrel Channa punctatus (Bloch, 1793) from River Gomti of Lucknow region, Uttar Pradesh, India

Abstract: A total of 187 samples of Channa punctatus (Bloch, 1793) from River Gomti of Lucknow region, Uttar Pradesh were studied during 2011. The sex ratio of 1: 0.84 was not significantly different from 1:1. Monthly variation in the gonadosomatic index (GSI) and maximum number of stage IV gonads encountered in the months of May to August indicated that the spawning season extends for about 4 months and spawning was high during the monsoon season. Absolute fecundity varied from 11000 to 28000, with an average value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
3
5
0
Order By: Relevance
“…Taslim et al (2002) pointed out that the co-efficient of correlation between fecundity versus TL and BW were found to range from 0.34-0.45 and 0.33-0.59 respectively in M. aculeatus. Similar observations were reported by many authors such as Das et al (1989) in Heteropneustes fossilis, Khan et al (2002) in Plotosus canius, Rheman et al (2002) in Liza parsia and by Kashyap et al (2016) in Channa punctatus. The finding of this study could be useful for management of the M. aculeatus stocks in the wild populations as well as under captive culture conditions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Taslim et al (2002) pointed out that the co-efficient of correlation between fecundity versus TL and BW were found to range from 0.34-0.45 and 0.33-0.59 respectively in M. aculeatus. Similar observations were reported by many authors such as Das et al (1989) in Heteropneustes fossilis, Khan et al (2002) in Plotosus canius, Rheman et al (2002) in Liza parsia and by Kashyap et al (2016) in Channa punctatus. The finding of this study could be useful for management of the M. aculeatus stocks in the wild populations as well as under captive culture conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Male dominancy over female may be due to accidental or natural mortality such as spawning stress of females in the population. reported by Abujam and Biswas (2011) and Kashyap et al (2016). However, it is worth mentioning here that several other workers (Qayyum and Qasim, 1964;Cardoso et al 2019) recorded the dominance of females over males.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The observed sex distribution among the species showed preponderance of males over females in their population. The sex ratio recorded in this study is in compliance with the works of Achakzai et al [36] in Manchar Lake, Kashyap et al [37] in Gomti River and Lawal et al [38] in Epe Lagoon.…”
Section: Resultssupporting
confidence: 90%
“…Shafi and Yousuf [41] reported positive allometric growth for males (3.07) and negative allometric for females (2.77) in Schizothorax niger from Dal lake. In contrast, Kashyap et al [37] reported allometric growth for males and females from India with b value 2.95 (males) and 3.13 (females).…”
Section: Resultsmentioning
confidence: 93%